Zerumbone, a Sesquiterpene, Controls Proliferation and Induces Cell Cycle Arrest in Human Laryngeal Carcinoma Cell Line Hep-2. (3rd July 2016) - Jegannathan, Srimathi Devi; Arul, Santhosh; Dayalan, Haripriya
ABSTRACT: Zerumbone (ZER), a sesquiterpene found in Zingiber zerumbet Smith, has been shown to possess antiproliferative, anticancer, antioxidant, and anti-inflammatory activity against various types of human carcinoma. The molecular mechanism by which ZER mediates its activity against many cancer types is revealed by many studies. Upregulation of proapoptotic molecules and suppression of antiapoptotic gene expression are few of the mechanisms by which ZER mediates its effect. The present study is focused on investigating the effect of ZER on proliferation of laryngeal carcinoma cells (Hep-2). MTT assay results showed that ZER (0.01–100 μM) induced death of Hep-2 cells in a concentration-dependent manner; significant suppression of proliferation of Hep-2 cells was seen with a IC50 value of 15 µM. ZER at a concentration of 15 and 30 μM for 48 h showed early signs of apoptosis as evidenced by confocal microscopy imaging. Flow cytometry studies showed that ZER induced cell cycle arrest. ZER arrested Hep-2 proliferation at S and G2/M phases of cell cycle. In conclusion, these results indicate that ZER has antiproliferative effect and arrests cell cycle in Hep-2 cells in vitro. This could be a potential anticancer drug against laryngeal carcinoma.